Capture efficiency of magnetically labeled particles traveling through an intracranial aneurysm - Cardona, Melisa; Benavides-Moran, Aldo; Ramirez, Juan (Zielona Góra: Uniwersytet Zielonogórski)
Cell manipulation using external magnetic fields has been proposed to accelerate the neck reendothelization of saccular unruptured stented intracranial aneurysms. This work presents a computational fluid dynamics (CFD) model of a Saccular Brain Aneurysm that incorporates a helicoidal stent.
Keywords: endothelization; particle manipulation; computational fluid dynamics; magnetohydrodynamics